PROJECT APPROACH: FACILITATING ELEMENTARY SCHOOL STUDENTS IN READING - Dessy Dwi Dwi Yudha Santhi (Fakultas Sastra Universitas Negeri Malang, 2011)
Metaphors in a written discourse such as in letters using bahasa Indonesia can be derived from the metaphorical expressions used by the writers to the editors, showing conceptualization which is based on what they experience, feel, and think in their life.This paper aims at finding out the universality of the concepts shown by the metaphors and the users using the metaphors. Using nonparticipant observation with note-taking technique, the data are collected and chosen purposively. With distributional, referential, reflective introspective, and abductive inferential methods, the data are analyzed. The results indicate that metaphors can be grouped into universal, specific, and public ones due to the universality, specification of the concepts conveyed in, and the users using them. This implies that bahasa Indonesia conveys similar concepts as other languages in the world do which is caused by the experiences from different time and places encountered by Indonesians living in an agricultural country.